The Challenges of Diagnosing Drowning Death Case - Masreni, Kadek Rina; Riduvan, Josephine Passareta; Liando, Juan Matthew; Gotama, Juan Reynaldy; Christina, Karmenita (UNUSA Press, 2022)
Background: According to the World Health Organization (WHO), about 0.7% of deaths worldwide, or 500,000 deaths worldwide each year, are caused by drowning. Drowning is the leading cause of death worldwide in boys aged 5-14. In the United States, drowning is the second leading cause of accidental death among children ages 1 to 4 years, with an average death rate of 3 per 1000 people. Based on the latest definition from WHO in 2002, drowning is a process of respiratory distress caused by submersion or immersion in liquid. Most drowning victims who drink only a small amount of water usually get better on their own. Less than 6% of drowning victims require hospital treatment. If the drowning victim is rescued as soon as possible, the subsequent drowning process can be prevented, which means it will not be fatal. Objective: To determine the challenges of dignosis of drowning death case at Bhayangkara Pusdik Sabhara Porong Hospital in 2021-2022. Methods: The study used a retrospective descriptive method. The research sample used was medical record data for drowning victims examined at Bhayangkara Pusdik Sabhara Porong Hospital in 2021-2022. Results: The study sample consisted of 5 dead bodies. The autopsy findings of drowning victims are cadaveric spasm, the sign of asphyxia, froth in the mouth/nose, abrasion, washerwoman's hands, enlarged lungs, Paltauf's spots, and froth in the airways. Conclusion: The challenges of diagnosing drowning death case at Bhayangkara Pusdik Sabhara Porong Hospital are mostly the dead bodies found in decomposed stage and unavailability of laboratory data. The diagnosis of drowning based on the results of the examination of signs of asphyxia, cadaveric spasm, and mostly froth was found in the respiratory tract.